Signs of Impact Effects in Time Series Regression Models - M. Hashem Pesaran; Ron P. Smith (Center for Economic Studies and ifo Institute (CESifo), 2013)
In this paper we consider the problem of interpreting the signs of the estimated coefficients in multivariate time series regressions where the regressors are correlated. Using a continuous time model, we argue that focussing on the signs of individual coefficients in such regressions could be misleading and argue in favour of allowing for the indirect effects that arise due to the historical correlations amongst the regressors. For estimation from discrete time data we show that the sign of the total impact, including the direct and indirect effects, of a regressor can be obtained using a simple regression that only includes the regressor of interest.
Keywords: C10; C50; 330; regression coefficients; impact effects